BYBELKUNDELEERPLANNE BY SKOLE - Lategan, Bernard C. (Scriptura, 1982)
Biblical studies in schools This report is the result of a consultation between the Department of Biblical Studies of the Universities of Stellenbosch and Western Cape and the Department of Religious Studies of the University of Cape Town on the problems of Biblical Studies in school. The consensus was that a much more life-centred approach is needed, emphasizing the relevance of the subject for the problems of modern society and especially for the complex South African scene and in providing the pupil with a set of values to cope successfully with a situation of rapid cultural change.